2013
DOI: 10.1016/j.soilbio.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence variation and methylation in an arsenic tolerant earthworm population

Abstract: 30Evidence is emerging that earthworms can evolve tolerance to trace element enriched soils. However, few 31 studies have sought to establish whether such tolerance is determined through adaption or plasticity. Here we 32 report results from a combined analysis of mitochondrial (cytochrome oxidase II, COII), nuclear (amplified

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 53 publications
2
51
0
Order By: Relevance
“…Unfortunately, their study was based on RAPD profiles, so it is impossible to infer if these genotypes correspond to particular A. caliginosa mitochondrial lineages. Similar phenomena have also been reported for other earthworm species: e.g., Kille et al (2013) demonstrated that two cryptic lineages of L. rubellus react differently to soil contamination by arsenic. However, in this study we observed no obvious patterns of habitat preference in A. caliginosa lineages.…”
Section: Discussionsupporting
confidence: 85%
“…Unfortunately, their study was based on RAPD profiles, so it is impossible to infer if these genotypes correspond to particular A. caliginosa mitochondrial lineages. Similar phenomena have also been reported for other earthworm species: e.g., Kille et al (2013) demonstrated that two cryptic lineages of L. rubellus react differently to soil contamination by arsenic. However, in this study we observed no obvious patterns of habitat preference in A. caliginosa lineages.…”
Section: Discussionsupporting
confidence: 85%
“…Cardinale et al (32) suggested two ways that disturbance can moderate relationships between biodiversity and ecosystem functioning: it can increase the chance that diversity generates unique system properties, and it can suppress the probability of ecological processes being controlled by a single taxon. Urbanization not only modifies existing disturbance regimes (e.g., fire and flood management), it also creates novel disturbances including disrupted dispersal pathways or stressors, ecotoxins and pollutants (33,34). Examples of phenotypic changes in response to new toxins include earthworms' tolerance to metals (33) and changes in endocrine systems of fish and birds (34).…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization not only modifies existing disturbance regimes (e.g., fire and flood management), it also creates novel disturbances including disrupted dispersal pathways or stressors, ecotoxins and pollutants (33,34). Examples of phenotypic changes in response to new toxins include earthworms' tolerance to metals (33) and changes in endocrine systems of fish and birds (34). Low statistical power might have hindered a stronger observed effect.…”
Section: Discussionmentioning
confidence: 99%
“…According to Sechi (2013), speciation within the L. rubellus taxon may have first arisen through allopatric speciation during the last European glaciation event whereby lineages were geographically isolated into separate refugia during the glacial period, followed by secondary contact between lineages in the post-glacial period. The two lineages have remained genetically distinct despite living in sympatry (Andre et al, 2010), but differ in subtle aspects of phenotypic expression, such as disparate responses to high levels of arsenic exposure (Kille et al, 2013) or minor morphological traits (Donnelly et al, 2014).…”
Section: Introductionmentioning
confidence: 99%